2008
DOI: 10.1001/archpsyc.65.12.1429
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of College Students and Their Non–College-Attending Peers

Abstract: Context Although young adulthood is often characterized by rapid intellectual and social development, college-age individuals are also commonly exposed to circumstances that place them at risk for psychiatric disorders. Objective To assess 12-month prevalence of psychiatric disorders, sociodemographic correlates, and rates of treatment among individuals attending college and their non-college attending peers in the United States. Design, Setting, Participants Face-to-face interviews were conducted in the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
519
5
18

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,258 publications
(611 citation statements)
references
References 60 publications
(59 reference statements)
20
519
5
18
Order By: Relevance
“…The percentage of these students in colleges and universities varies between 30% and 50% (Blanco et al, 2008;Eisenberg, et al, 2007); many of these students may have other comorbidities.…”
Section: Students With Mental Health Related Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of these students in colleges and universities varies between 30% and 50% (Blanco et al, 2008;Eisenberg, et al, 2007); many of these students may have other comorbidities.…”
Section: Students With Mental Health Related Disabilitiesmentioning
confidence: 99%
“…For example, a large scale American study showed that among college and university students aged 19 to 25, "almost half of college-aged individuals had a psychiatric disorder in the past year" (Blanco et al, 2008(Blanco et al, , p. 1429, although almost 30% had a psychiatric diagnosis of substance use disorder. Blanco et al also reported that only 25% of students had sought treatment.…”
Section: Students With Mental Health Related Disabilitiesmentioning
confidence: 99%
“…One epidemiological study 30 reports that students are more prone to experience alcohol-related problems when compared to nonstudents and are twice as likely to develop disorders related to alcohol and other drugs than the remaining American population. Accessibility is a complex and subjective concept that partly depends on the individuals' economic resources.…”
Section: /8mentioning
confidence: 99%
“…Anxiety disorders, alcohol abuse, and other mental health disorders are strikingly common among university-age people. 15 The Secrets Wall is one of several activities offered at the University of Iowa Main Library to support undergraduate students during final exams. Although originally launched as a means of stress relief, the Secrets Wall also offers an alternative form of casual peer education, with opportunities for reflection and conversation.…”
Section: Kelly: the Secrets Wall At The University Of Iowamentioning
confidence: 99%